2014
DOI: 10.3758/s13414-014-0744-x
|View full text |Cite
|
Sign up to set email alerts
|

Finding faces among faces: human faces are located more quickly and accurately than other primate and mammal faces

Abstract: We tested the specificity of human face search efficiency by examining whether there is a broad window of detection for various face-like stimuli—human and animal faces—or whether own-species faces receive greater attentional allocation. We assessed the strength of the own-species face detection bias by testing whether human faces are located more efficiently than other animal faces, when presented among various other species’ faces, in heterogeneous 16-, 36-, and 64-item arrays. Across all array sizes, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Another study found differences in infants' sensitivity to gaze in human and nonhuman stimuli: 12‐month‐olds looked longer to, and were better at gaze following, when observing videos of humans compared to apes (Kano & Call, ). We also found our infants looked longer to human than animal faces (Prediction 3b), consistent with studies in adults, reporting privileged detection of conspecifics (Simpson, Buchin, et al, ; Simpson, Husband, Yee, Fullerton, & Jakobsen, ; Stein, Sterzer, & Peelen, ). Our findings of an early own‐species bias suggest that infants have already specialized for processing conspecific faces by 2 to 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another study found differences in infants' sensitivity to gaze in human and nonhuman stimuli: 12‐month‐olds looked longer to, and were better at gaze following, when observing videos of humans compared to apes (Kano & Call, ). We also found our infants looked longer to human than animal faces (Prediction 3b), consistent with studies in adults, reporting privileged detection of conspecifics (Simpson, Buchin, et al, ; Simpson, Husband, Yee, Fullerton, & Jakobsen, ; Stein, Sterzer, & Peelen, ). Our findings of an early own‐species bias suggest that infants have already specialized for processing conspecific faces by 2 to 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
“…This facilitated processing of human faces is known as an own-species bias (Scott & Fava, 2013). Already by 6 months, infants, like adults, are more likely to detect, more quickly detect, and look longer at human than animal faces in in complex arrays (Gluckman & Johnson, 2013;Jakobsen et al, 2016;Simpson, Buchin, Werner, Worrell, & Jakobsen, 2014a), suggesting an own-species bias for face detection may emerge early in development. In fact, newborns may even display an early bias for human compared to animal faces (Heron-Delaney, Wirth, & Pascalis, 2011).…”
Section: E Xperien Ce Drive S Infants' Face S Pecializ Ati On: Own mentioning
confidence: 99%
“…Given the social and ecological importance of faces for infants, and their early exposure to conspecifics, biases to detect conspecific faces may be evident in the first year of life (Simpson et al, ). In adults, conspecific faces are detected more efficiently than heterospecific faces (Simpson et al, ; 2014c). The present study explored whether this OSB in face detection is present in 6‐ and 11‐month‐old infants.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, animal faces engage similar visual processing as human faces (Diamond & Carey, 1986) and elicit similar neural activation (Blonder et al, 2004); therefore, comparisons of human and animal face processing can disentangle developmental patterns in face processing generally from human face processing specifically (Whyte, Behrmann, Minshew, Garcia, & Scherf, 2015). While adults exhibit an OSB in face detection (Simpson, Buchin, Werner, Worrell, & Jakobsen, 2014a), it is unclear when this bias emerges.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual narrowing impacts one’s ability to discriminate non-native exemplars (i.e., one face from another face) from infancy through adulthood (e.g., Mondloch, Maurer, & Ahola, 2006; Pascalis et al, 2002), and therefore, it also affects target selection in visual search tasks (Simpson, Buchin, Werner, Worrell, & Jakobsen, 2014). Results from visual search tasks can provide evidence for the mechanism underlying the reduced sensitivity with non-native stimuli.…”
Section: Introductionmentioning
confidence: 99%